The first troglobitic species of the extraordinary genus Pandirodesmus Silvestri, 1932 from the Brazilian Amazon (Polydesmida, Chelodesmidae, Pandirodesmini) - Romero-Rincon, Juan; Bouzan, Rodrigo S.; Ferreira, Rodrigo L. (Zootaxa, 2025)
Pandirodesmus zogbiae sp. nov. is described as the first strictly troglobitic species of the genus and it represents the first record of both the genus and the tribe in Brazil. Specimens were collected from Paraíso Cave, the largest known limestone cave in the Amazon, located in Pará State. The species is distinguished by a unique combination of morphological characters, including slight heteropody, the presence of claws on all legs, concave microsculptures on the posterior rings, and a unique gonopodal conformation. In addition to a detailed morphological description, a key to species of the genus and a distribution map are provided.